Fish oil supplementation to rats fed high-fat diet during pregnancy prevents development of impaired insulin sensitivity in male adult offspring - Albert, Benjamin B. (Sci Rep, 2017)
We examined whether maternal fish oil supplementation during pregnancy could prevent development of insulin resistance in adult male offspring of rat dams fed a high-fat diet. Time-mated Sprague-Dawley rat dams were randomised into four treatment groups: Con-Con, dams fed a control diet (fat: 15% kcal) and administered water by gavage; Con-FO, control diet with unoxidised fish oil by gavage; HF-Con, high-fat diet (fat: 45% kcal) and water by gavage; and HF-FO, high-fat diet and unoxidised fish oil by gavage. Dams were fed the allocated diet ad libitum during pregnancy and lactation, but daily gavage occurred only during pregnancy. After weaning, male offspring consumed a chow diet ad libitum until adulthood. Maternal high-fat diet led to increased food consumption, adiposity, systolic blood pressure, and triglycerides and plasma leptin in adult HF-Con offspring. HF-Con offspring also exhibited lower insulin sensitivity than Con-Con rats. Male offspring from HF-FO group were similar to HF-Con regarding food consumption and most metabolic parameters. However, insulin sensitivity in the HF-FO group was improved relative to the HF-Con offspring. Supplementation with unoxidised n-3 PUFA rich oils in the setting of a maternal obesogenic diet improved insulin sensitivity, but had no impact on body composition of adult male offspring.